De la Urbe: percepciones de docentes y estudiantes sobre el laboratorio de periodismo de la Universidad de Antioquia - Forero Arango, Ximena; Arias Hidalgo, Walter (Folios, revista de la Facultad de Comunicaciones y Filología, 2025)
This text is the result of a study that, through a constructivist methodology and a qualitative approach, aimed to understand the perceptions of students and professors of the undergraduate Journalism program at the Universidad de Antioquia regarding De la Urbe (DLU), the program’s media laboratory. The results show that, although DLU is viewed positively (with an average score of seven out of ten), challenges persist in terms of its perception as a closed space, low student participation (a median of three out of ten) and editorial processes that could be clearer. The findings highlight the need to improve integration with the undergraduate curriculum, open up the editorial board, and standardize publication processes. This study un derscores the importance of DLU as a formative component and proposes actions to strengthen its procedures and promote greater inclusion and participation of the academic community.